ENGLISH AS A FOREIGN LANGUAGE (EFL) TEACHERS’ PERCEPTION ON INFORMATION AND COMMUNICATION OF TECHNOLOGY (ICT) - Ega Mahfira; Nurdevi Bte Abdul; Ratu Yulianti Natsir (Universitas Muhammadiyah Makassar, 2019)
This research aimed to find out kinds of information and communication of technology (ICT) is used by the teachers’ to teach English at SMP NEGERI 2 MASAMBA and to find out Teachers’ perception on the use of information and communication of technology (ICT) in teaching English. This research used a descriptive qualitative method, the instruments used were observation and interview. The observation was used to observe and interview the English teachers. The findings of the research showed the results of the teachers’ interview showed that mostly the teacher gave positive perception and agreed toward and teachers’ used Information and Communication Of Technology (ICT) in teaching English, they were happy, they left easy to understand the lesson, motivated to learn, being polite, diligent doing assignment. Whereas, some student was unhappy in learning English and got difficulties to understand the lesson because the thought that learning English was difficult.